A review on the effect of different types of organic fertilizer towards oil palm growth / Norliyana Mohd Rafi - Mohd Rafi, Norliyana (Faculty of Plantation and Agrotechnology, 2017)
Oil Palm (Elaeis guinensis) need sufficient nutrients for field optimal performance at all stage. The fertilizer management is very important to make sure the quality and productivity of oil palm with minimum cost since the higher cost in plantation is manuring. Every organic fertilizer has their own nutrient content that a plant needs. My objectives are to determine the suitable application rate of different organic fertilizer towards growth, to increase yield and productivity and reduce production costs, the identity the potential growth and productivity of oil palm, to identify the potential growth and productivity of oil palm based on application of organic fertilizer or soil amendments and to compare the nutrient content between different organic fertilizer. Although POME and animals waste have a little bit nutrient than empty fruit bunch and bio compost but it can improve the soil fertility, organic matter and soil structure. The characteristics and absent of soil amendments can help process water uptake and mineral absorption from roots. Based on my review soil amendment application can increase leave population, plant height and stem girth at nursery stages where the stages need more nutrient than other stages.